Making the effect visible – OX40 targeting nanobodies for in vivo imaging of activated T cells - Frecot, Desiree I.; Blaess, Simone; Wagner, Teresa R.; Kaiser, Philipp D.; Traenkle, Bjoern; Fandrich, Madeleine; Jakobi, Meike; Scholz, Armin M.; Nueske, Stefan; Schneiderhan-Marra, Nicole; Gouttefangeas, Cécile; Kneilling, Manfred; et al. (Frontiers in Immunology, 2024)
Purpose: Human OX40 (hOX40/CD134), a member of the TNF receptor superfamily, is mainly expressed on activated T lymphocytes. Triggered by its ligand OX40L (CD252), it provides costimulatory signals that support the differentiation, proliferation and long-term survival of T cells. Besides being a relevant therapeutic target, hOX40 is also an important biomarker for monitoring the presence or infiltration of activated T cells within the tumor microenvironment (TME), the inflammatory microenvironment (IME) in immune-mediated diseases (IMIDs) and the lymphatic organs. Here, we developed novel single domain antibodies (nanobodies, Nbs) targeting hOX40 to monitor the activation status of T cells by in vivo molecular imaging.Methods: Nbs against hOX40 (hOX40-Nbs) were selected from an immunized Nb-library by phage display. The identified hOX40-Nbs were characterized in vitro, including determination of their specificity, affinity, stability, epitope recognition and their impact on OX40 signaling and T cell function. A lead candidate was site-specifically conjugated with a fluorophore via sortagging and applied for noninvasive in vivo optical imaging (OI) of hOX40-expressing cells in a xenograft mouse model.Our selection campaign revealed four unique Nbs that exhibit strong binding affinities and high stabilities under physiological conditions. Epitope binning and domain mapping indicated the targeting of at least two different epitopes on hOX40. When analyzing their impact on OX40 signaling, an agonistic effect was excluded for all validated Nbs. Incubation of activated T cells with hOX40-Nbs did not affect cell viability or proliferation patterns, whereas differences in cytokine release were observed. In vivo OI with a fluorophore-conjugated lead candidate in experimental mice with hOX40-expressing xenografts demonstrated its specificity and functionality as an imaging probe.Considering the need for advanced probes for noninvasive in vivo monitoring of T cell activation dynamics, we propose, that our hOX40-Nbs have a great potential as imaging probes for noninvasive and longitudinal in vivo diagnostics. Quantification of OX40 + T cells in TME or IME will provide crucial insights into the activation state of infiltrating T cells, offering a 4 valuable biomarker for assessing immune responses, predicting treatment efficacy, and guiding personalized immunotherapy strategies in patients with cancer or IMIDs.